Traditional Use of Indigenous Plants in Betul District Of Madhya Pradesh to Cure Diarrhoea and Dysentry - Sapan Patel (Environment Conservation Journal, 2010)
A survey of medicinal plants of different rural and forest area of Betul district was conducted. It was found that the drug preparation of plant origin is commonly used by tribal local inhabitants and folk practitioners for the treatment of diarrhoea and dysentery disease. About 7 plant species belonging to 6 families are described along with the method of drug preparation mode of administration probable Degases and duration of treatment. The aim to study is not only to prescribe the remedies for disease in human beings but also an endeavour to draw attention for the need of a detailed study on medicinal plants of the area, which could provide better and efficient remedies for diarrhoea, dysentery and many other dreadful diseases. The paper enumerates the traditional uses of more than 50 plants used by tribes inhibiting the Betul District. Information on the medicinal and other traditional uses gathered from the tribal together with their botanical identity is presented. The indigenous traditional knowledge of medicinal plants of various ethnic communities, where it has been transmitted orally for centuries is fast disappearing from the face of earth due to advent of modern technology and transformation of traditional culture. The collection of information about natural flora, classification, management and use of plants by the people holds importance among the ethno botanists.